Effect of indomethacin on cytoprotection Centaurea solstitialis extract against stress -induced gastric ulcers in mice (Veterinary Science, 2017)
A certain number of prostaglandins (PGs.) and synthetic analogs protect the gastrointestinal mucosa against noxious agents. To study the participation of enddgénous PGs. on the cytoprotection that produce Centaurea solstitialis L., Compositae (n.v. Abrepuño) extracts, indomethacin as blocking agent of the PGs. synthesis was used. Residues of methanolic and chloroformic extracts of flowers of the plant with excipients mixture Tween 80 (T 80) and Carboxymethyl cellulose (CMC), were administered by gastric catheter to female mice inmediately before subjecting them to stress by water immersion. A 5 mice group was administered T 80 + CMC (a). Another 4 groups, of equal number of animals, were treated with methanolic (b,c) and chloroformic (d,e) extracts. Groups a, e and e, received a subcutaneous dosis ofindometacin (5 mg/kg) each, 1 hour before the bioassay. Four and a halfhours later, the animals were sacrified. The stomachs were removed and insufflated with formol at 10 % and they were sumerged for 24 hours in this solution, afterwards they were opened by the major 16 curvature, to observe lessions. The stomachs were phtographied and the ulcering area (mm2) was determined by means of an image analyzer. Percentages of inhibition (PI) produced by the extracts in groups b, e, d and e compared with the control group a, were calculated. The PI were 100 %; 98.13 %; 91.89 % and 48.74 % for the groups b, e, d and e, respectively. The difference found between the groups d and e (p0.05) would implicate an important partial participation of the PGs. in the cytoprotector mechanism of action of the chloroformic extract. Meanwhile, flavonoids, among them kaempferol, present in the methanolic extracts of the plant, showed a moderate effect which would complement with the effects of other components of this fraction, and would allow to state the posibility of a mechanism of action independent of PGs
Keywords: Gastric cytoprotectin; Indometacina; Medicinal plant